Promoting Language Learning through a Thematic Vocabulary-Based Syllabus in Different Grades - Yanilis Romero (Universidad de La Sabana, 2009)
This research explores a thematic vocabulary-based syllabus, which can help public and private schools develop good practice of English as a foreign language teaching for different audiences. Additionally this paper proposes possible approaches for teaching English content. The researcher considered communicative trends to create dynamic teaching settings and used data collection techniques such as: interviews, class observation, need analysis, questionnaires, video recording, and stimulated recall. This five-month action research project analyzed the application of the thematic vocabulary-based syllabus. Three main findings can be reported. First, the use of a thematic vocabulary-based syllabus enhanced learning and promoted motivation. Second, oral production was increased while students were taught using content of their preference. Third, the content of the area is more interesting when learners are participants in the selection of the topics to be taught; students' participation was active since they could use their prior knowledge during the classes.